A RETROSPECTIVE INVESTIGATION OF BLOOD COAGULATIVE PARAMETERS PT, KPTT, PROTEIN C, AND ANTITHROMBIN III IN 95 PATIENTS WITH LIVER DISEASE - George Zhu; Broekmans AW; Bertina RM (Universal Journal of Pharmaceutical Research, 2025)
Background: The liver is a crucial synthesis of blood coagulation factors and anticoagulative serine proteases such as protein C(PC) and antithrombin III (ATIII), which exerts a key role in the regulation of hemostatic balance. Activated protein C(APC) and protein S complex inactivate the activated factor Va and VIIIa, thus limiting Xa and thrombin formation. The excess protein S can drive cancer cellular proliferation and cell survival through oncogenic receptor Axl. In presence of heparin binding, antithrombin III (ATIII) and thrombin form an inactive complex in a 1:1 molar ratio. ATIII also inactivate factor IXa, Xa, XIa and XIIa at slow rate. In the setting of liver diseases, this reduced dysregulation can be attributed to decreased synthesis by the liver and increased consumption of coagulative factors and protein C and ATIII. Methods: In current study, using routine detection for the blood coagulative parameters in 75 patients with liver diseases. Results: The results showed that there exist one or three coagulative parameters PT, KPTT, and TT abnormal longer. Moreover, the abnormal intensity of coagulative parameters was associated to the severity of liver diseases. In our detection of 20 liver cirrhosis, the results showed significantly decreased plasma protein C antigen (PC:Ag 0.5501 vs 1.0578 µ/ml) and antithrombin III level (ATIII: Ag 21.8 vs 39.8 mg/dl, ATIII:C 40.25 vs 105.04%), respectively. Conclusions: The measurement of multidispillary analyses of coagulative and anticoagulative system protein C and ATIII level are helpful to monitoring the liver diseases and might play a predictable marker. Peer Review History: Received 13 September 2024; Reviewed 20 November; Accepted 26 December; Available online 15 January 2025 Academic Editor: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Reviewers: Dr. Vanina Doris Edo’o, University of Yaounde I, Yaounde, Cameroun, vanina_edoo@yahoo.com Dr. Taiwo O Elufioye, University of Ibadan, Nigeria, toonitaiwo@yahoo.com